Research handbook on political representation - Cotta, Maurizio 1947-; Russo, Federico 1978- (Edward Elgar Publishing Limited, 2020)
"At a time when political representation can be said to be facing its ultimate crisis, this crucial work clarifies the terms of the debate, providing an up-to-date analysis of the main conceptual and institutional controversies that have arisen surrounding this topic. Written by leading scholars in the field, contributions focus on how representation is conceptualised and its relation to democracy, examining how political institutions in different historical periods (ranging from the middle ages to the modern day) have ensured representation based on demands of various social forces. This Research Handbook also encapsulates the directions taken by the main strands of empirical research in political representation within the context of liberal democracies and beyond. Overall, this provides a major contribution to the growing understanding of one of the most important institutional inventions of contemporary politics. The Research Handbook on Political Representation is a comprehensive and agile guide to the main bodies of literature on representation for academic researchers in political science, sociology and history. It will also guide post-graduate and graduate students of the same fields in the exploration of the crucial research questions arising from the concept and reality of political representation"--Back cover
Keywords: Repräsentation -- Politik; Representative government and representation; Aufsatzsammlung